Cost-Benefit Analysis of Robotic Versus Nonrobotic Minimally Invasive Mitral Valve Surgery. Issue 2 (March 2015) - Hassan, Mohammed; Miao, Yongjie; Lincoln, Joy; Ricci, Marco
<x xml:space="preserve">Abstract</x> Objective To date, a direct comparison of minimally invasive mitral valve repair or replacement (mini-MVR) versus robotic MVR is lacking; therefore, the purpose of this study was to address this deficit and compare mini-MVR with robotic MVR from a cost-benefit perspective. Methods From a total of 759 literature citations, 21 studies were included for statistical comparisons of benefit outcomes, whereas 3 studies and our institutional experience were used to compare costs. Results The total cost per case exceeding that of conventional MVR is approximately 2063.90 for robotic MVR and 271 for mini-MVR. Mean 30-day mortality rates for mini-MVR and robotic MVR groups were 1.24% and 0.55%, respectively [106/8548 vs 6/1089; odds ratio (OR), 2.27; P = 0.052]. The conversion rate to conventional MVR was 0.77% in mini-MVR and 1.83% in robotic MVR (35/5092 vs 22/1046; OR, 0.32; P < 0.001). The rate of neurologic events was 1.32% in mini-MVR and 2.37% in robotic MVR (109/8257 vs 20/845; OR, 0.55; P = 0.02). Postoperative atrial fibrillation was seen in 11.42% of mini-MVR patients and in 19.67% of robotic MVR patients (371/3249 vs 203/1032; OR, 0.53, P < 0.001). Mean cardiopulmonary bypass time was longer in mini-MVR (137.4 vs 130.4 minutes), whereas cross-clamp time was shorter (82.2 vs 96.7 minutes). Conclusions Our comparative analysis provides insights into the clinical benefits versus variable costs relationship related to mini-MVR and robotic MVR.